Digital Marketing Strategy, Marketing Communication, and Service Quality: Their Impact on Wardah Cosmetics Consumer Satisfaction in The Age Range of 18-40 Years - Arfah, Lita (Universitas Muhammadiyah Prof. DR HAMKA., 2024)
The aim of this study is to see how the satisfaction of Wardah cosmetics customers in Pekanbaru, who are between the ages of 18 and 40, is influenced by digital marketing strategies, marketing communications, and quality of service. Using the purposive sampling method, 238 people who used Wardah products and had access to digital media were selected. Independent variables determine consumer satisfaction, which is measured through the questionnaires used for data collection. Data analysis is carried out using Pearson correlation methods to evaluate the strength of the relationship between independent variables and customer satisfaction. The results of the research showed that digital marketing strategies and consumer satisfaction had a significant positive correlation with a correlative coefficient of 0.65 (p = 0.001), marketing communications also had a positive corelation with the correlational factor of 0.58 (p= 0.005), and the quality of service has a positive Correlation of 0.72 (p_0.005). The study found that Wardah cosmetics customers in Pekanbaru, especially customers between the ages of 18 and 40 years, were very satisfied with digital marketing strategy, marketing communication, and service quality. This conclusion provides practical implications for companies to create more effective marketing and service strategies to increase customer loyalty and satisfaction.